Investigating the determinants of competitiveness of the footwear industry of Bangladesh: An ARDL approach - Shams, Aditi; Tamanna, Ashia Khatun (International Journal of Asian Social Science, 2025)
This empirical study aims to investigate the factors determining the competitiveness and comparative advantage of the footwear industry in Bangladesh. A two-stage methodology was employed, including a novel dataset from the year 2001 to 2022. In the first stage, this study employs Revealed Comparative Advantage (RCA), Revealed Symmetrical Comparative Advantage (RSCA), Relative Trade Advantage Index (RTAI), Revealed Import Advantage Index (RIAI), Net Export Index (NEI), and Export Market Share (EMS) to identify the comparative and competitive advantages of the footwear sector in Bangladesh. In the second stage, this study applies the Autoregressive Distributed Lag (ARDL) model to evaluate the determinants of competitiveness spanning from 2001 to 2022. The findings reveal a sustained comparative advantage of the footwear sector in Bangladesh. The ARDL examination discloses that economic growth and trade openness have a significant positive association with footwear competitiveness, both in the long and short term. Human capital, trade freedom, and institutional quality also have a significant association with footwear competitiveness. These findings reveal that the footwear sector in Bangladesh has the potential to significantly contribute to the overall export growth of the country. Policymakers, industry stakeholders, investors, and trade organizations should take sustainable measures to utilize this competitiveness and focus on taking facilitative measures to diversify the current export basket of Bangladesh.